2020
DOI: 10.1177/2380084420981016
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss and Nutritional Status in Older Adults: A Systematic Review and Meta-analysis

Abstract: Background/Objective: Older adults are at risk for tooth loss and compromised nutritional status. Our objective was to conduct a systematic review and meta-analysis to answer the following question: Among adults aged ≥60 y living in developed countries, what are the associations between tooth loss and nutritional status as assessed by a validated nutrition screening or assessment tool? Methods: PRISMA guidelines were followed. PubMed, Scopus, CINAHL, Web of Science, and MEDLINE were searched for studies publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 22 publications
2
67
0
3
Order By: Relevance
“…The attenuation of the within-person differences in cognitive decline between individuals with and without dentures after adjusting for BMI could be supported by the aforementioned nutritional pathway. Tooth loss has been associated with nutrient intake and nutritional status, 4 and although the use of dental prostheses might not fully compensate for the masticatory function, it can mitigate its impact on nutrition by favoring food selection and nutrient intake. 23 Besides difficulties in eating, tooth loss without replacement can affect social aspects of daily living, such as embarrassment when smiling, laughing or showing their teeth, and speech problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attenuation of the within-person differences in cognitive decline between individuals with and without dentures after adjusting for BMI could be supported by the aforementioned nutritional pathway. Tooth loss has been associated with nutrient intake and nutritional status, 4 and although the use of dental prostheses might not fully compensate for the masticatory function, it can mitigate its impact on nutrition by favoring food selection and nutrient intake. 23 Besides difficulties in eating, tooth loss without replacement can affect social aspects of daily living, such as embarrassment when smiling, laughing or showing their teeth, and speech problems.…”
Section: Discussionmentioning
confidence: 99%
“…2 The associated significant financial and human costs to countries, societies, families and individuals pave the way to the need for further research aimed at identifying potential modifying risk factors to prevent or minimize cognitive decline and dementia. 1 A growing body of evidence suggests a relationship between cognitive impairment and dementia with tooth loss, as the latter is associated with various general health outcomes, such as diabetes 3 and nutrition, 4 that are known risk factors affecting cognitive decline. 5 However, previous systematic reviews found that this relationship is inconclusive, [6][7][8] highlighting the low-grade level of evidence and the need for further well-designed longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, tooth loss is a complex problem, potentially causing different effects. Nutrition is especially affected by the presence of remaining teeth, and tooth loss increases risk of malnutrition [ 26 ]. This might also increase RA disease activity, which is influenced by dietary factors as well [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Missing front teeth affects aesthetics and speech while multiple missing teeth affects chewing function [68]. Tooth loss resulted in edentulism or lack of functional dentition affects nutritional intake and poses an increased risk of malnutrition by 21% [71]. Tooth loss can provoke negative impacts on social status, self-esteem and oral health-related quality of life [72].…”
Section: Edentulismmentioning
confidence: 99%